MHR: Providing a new perspective in HR in terms of crisis management - Christina Nizamidou; Fotis Vouzas (International Journal of Business Science & Applied Management (IJBSAM), 2018)
Crises have become an integral part of everyday life. They affect humans, their communities, and their organizations. The tragedies, natural catastrophes, and other crises that occur worldwide threaten the public's welfare, people's mental and physical wellbeing, the prosperity and operational sustainability of organizations, and impose inestimable costs. Human beings may be harmed or affected by crises in their roles as consumers, stakeholders, and employees. Dealing with these events represents a challenging agenda, and particularly so for organizations' Human Resource Departments (HRDs). The authors of this paper explore the strategic role of HRDs in crisis management by adopting a theoretical perspective and synthesizing relevant literature in the crisis management field. This analysis offers valuable insights into the HRD's new Mentor-Healer-Renaissance Man (MHR) role for managing crisis situations. As a member of the Crisis Management Team (CMT), the HRD is responsible for providing leadership to an organization and its employees in the event of a crisis, by implementing predetermined actions intended to maintain the company's operations, and responding to its employees physical, psychological, and emotional needs. This article's novelty and practical contribution is drafting a policies and procedures manual that specifies the actions that are to be performed by the HRD before, during, and following a crisis. These procedures, which can be implemented by appropriate departments in a wide range of organizations, can be modified as needed, to be consistent with an organization's more general crisis management strategy.
Keywords: 650; crisis management; human resource management; new; role; strategic